Self-regulation and Tolerance for Uncertainty as Resources for the Subjective Well-being of Modern Youth: A Cross-cultural Aspect - Tatiana N. Banshchikova; Maksim L. Sokolovskii; Tatiana V. Korosteleova (RUDN Journal of Psychology and Pedagogics, 2022)
The study of the socio-cultural specifics of subjective well-being, its determinants and resources are an important task of modern psychology. The authors present the results of an empirical study, the purpose of which is to identify the features of the relationship between conscious self-regulation and tolerance for uncertainty and subjective well-being in young people of different ethnic groups. The study involved 1435 respondents aged 18-35 from five regions of Russia (Karachay-Cherkess Republic, Kabardino-Balkarian Republic, Republic of North Ossetia - Alania, Stavropol Territory, Moscow and the Moscow Region), belonging to the dominant ethnic groups in them. The design of the empirical study included an assessment of differences in indicators of subjective well-being, tolerance or intolerance for uncertainty and conscious self-regulation among various representatives of ethnocultural groups, as well as an analysis of the relationship between these indicators, in particular, using structural modeling. The results obtained confirm the influence of the cultural context of income on the level of subjective well-being. Less prosperous, as they consider themselves, are young people from ethnic groups where the socio-economic situation of the region does not provide opportunities for self-realization of the individual. The study has revealed two types of regulatory profiles: (1) a profile with a harmonious structure with a relatively pronounced general level of self-regulation, which is observed among the Russian respondents from Moscow and the Moscow region; and (2) a relatively accentuated profile, characteristic of Karachays, Circassians, Ossetians, and Russians (from the Stavropol Territory), expressed in the desire for a clear programming of their actions, their compliance with certain norms. It has been established that young people from the southern republics are less tolerant of uncertainty: they tend to solve problems in a situation of uncertainty in a ‘ready-made’ algorithm determined by traditions. Finally, the authors reveal the structure of relationships between the predictors of subjective well-being, which are presented in the form of models. The central place in these models belongs to conscious self-regulation and its basic cognitive-regulatory processes and personal-regulatory properties, which, both directly and indirectly, due to the mediator role of tolerance or intolerance for uncertainty, affect the subjective well-being of young people. The results of the study contribute to a deeper understanding of the ethno-regional specificity of the predictors of the subjective well-being of today’s youth and can serve as a basis for assisting in constructing interaction with representatives of other cultures and developing strategies for actively overcoming difficulties in a situation of uncertainty.